Bulk Synthesis of Monodisperse and Highly Biocompatible Poly(ɛ-caprolactone)-diol by Transesterification Side-Reactions. Issue 6 (13th April 2018) - Shahrousvand, Mohsen; Mir Mohamad Sadeghi, Gity; Salimi, Ali; Nourany, Mohammad
ABSTRACT: Ring-opening polymerization of ε-caprolactone was performed at 130°C, under partial vacuum in the presence of stannous octoate as the catalyst and 1, 4-butanediol as the initiator. After the termination of polymerization by deionized water, a hydroxyl group formed at the end of the polymer chains. Structure of the synthetic poly(ε-caprolactone)-diols (PCL-diol), molecular weight, polydispersity index, and Cell viability were evaluated. Very narrow distribution in the molecular weight obtained for PCL-diols is due to a new method for synthesis. It was shown that by the increase in PCL-diols, the compatibility of human mesenchymal stem cells grew up. GRAPHICAL ABSTRACT: